Dualistyczny model poznawczy heurystyki Daniela Kahnemana i Amosa Tversky’ego - Klepczarek, Emilia (Gospodarka w Praktyce i Teorii, 2012)
The paper conducts the collective specification of fallacies in the perception of reality made by market participants. It is based on the Daniel Kahneman and Amos Tversky’s esseys and it proves that the paradigm of rationality in human behaviour is actually a purely idealistic assumption and is often not reflected in the factual decisions made by consumers. The article pointed out numerous examples of so-called heuristics and biases, which cause the wrong estimation of the probability of certain events and thus are the reason of making non-optimal choices. The studies provide the evidence that unconscious, irrational, emotional and psychological factors are crucial in decision-making situations and to make the forecasts and projections more realistic they should be taken into account in the development of econometric models, business strategies or human resources management policy.